Respuesta :
Answer:
- (2b - 1)(2a + 3n)
-----------------------------------------------
Given polynomial
- 4ab + 6bn - 2a - 3n
Factorize it as below:
4ab + 6bn - 2a - 3n =
(4ab - 2a) + (6bn - 3n) = Regroup
2a(2b - 1) + 3n(2b - 1) = Factorize each group using common factors
(2b - 1)(2a + 3n) Factorize using common factor
Answer:
[tex](2b-1)(2a+3n)[/tex]
Step-by-step explanation:
Given expression:
[tex]4ab+6bn-2a-3n[/tex]
Factorize the first two terms and the last two terms separately:
[tex]\implies 2b(2a+3n)-1(2a+3n)[/tex]
Factor out the common term (2a + 3n):
[tex]\implies (2b-1)(2a+3n)[/tex]